Diagnosis, treatment and outcome following chronic encircling hobbling wounds in a group of working Donkeys in Morocco - Azelhak, Rabiaa; Kay, Gigi R.; Pollock, Patrick J. (Austral Journal of Veterinary Sciences, 2023)
Owners of working equids in Morocco, as in other low and middle-income countries hobble their animals around the pastern using different materials (wire, baling twine and ropes). Resulting wounds are very common and can cause serious damage. Some hobbles even embed into the soft tissue and bony structures of the pastern. Using a retrospective study of The American Fondouk hospital’s clinical records, the diagnosis, treatment and outcomes of embedding hobbling injuries are described. From 2012 to 2020, sixteen donkeys were presented suffering from unilateral severe lameness (4/5 to 5/5 lameness on AAEP scale) associated with hobble wounds. Circumferential wounds and/or fibrosis in the pastern were present in all these cases. Because of the suspicion of the presence of wire or baling twine, radiographs of the pasterns of all animals were routinely taken. Ten out of sixteen showed wire in situ encircling the pastern and the others showed a ghost outline of a baling twine hobble with similar periosteal reactions. All animals were treated by surgical removal of the hobble, wound flushing, systemic antibiotics, and bandaging. The outcome was good to excellent in all cases. In these authors’ knowledge, this is the first report in the literature of the diagnosis, treatment, and outcome of embedded hobbles in Equidae.